Effects of the molecule-electrode interface on the low-bias conductance of Cu-H2-Cu single-molecule junctions - SANVITO, STEFANO (My University, 2016)
The atomic structure and electronic transport properties of a single hydrogen molecule connected to both symmetric and asymmetric Cu electrodes are investigated by using the non-equilibrium Green’s function formalism combined with the density functional theory. Our calculations show that in symmetric Cu–H 2 –Cu junctions, the low-bias conductance drops rapidly upon stretching, while asymmetric ones present a low-bias conductance spanning the 0.2–0.3 G 0 interval for a wide range of electrode separations. This is in good agreement with experiments on Cu atomic contacts in a hydrogen environment. Furthermore, the distribution of the calculated vibrational energies of the two hydrogen atoms in the asymmetric Cu–H 2 –Cu junction is also consistent with experiments. These findings provide clear evidence for the formation of asymmetric Cu–H 2 –Cu molecular junctions in breaking Cu atomic contacts in the presence of hydrogen and are also helpful for the design of molec- ular devices with Cu electrodes
PUBLISHED
Export Date: 5 January 2017
Keywords: Cu electrodes; Cu electrodes